Genome-wide identification: molecular characterization and evolutionary aspects of Sox genes in Nile tilapia: Molecular characterization of Sox genes in N. tilapia - Khan, Muhammad Farhan; Sultana, Mehwish; Parveen, Shakeela; Hassan, Wardah; Tayyab, Muhammad; Mashahour Fawwaz Alenazi; Alanazi Khalid Zabena; Xu, Youhou; Hong, Zibin; Zhu, Peng; Shafique, Laiba (Cellular and Molecular Biology, 2025)
Nile tilapia has become one the most significant species in global aquaculture due to its exceptional adaptability, rapid growth and high reproductive capacity. Role of Sox genes in reproduction and development made attention to further investigate the role of these genes. Based on N. tilapia importance in aquaculture industry and role of Sox genes in the development of tissues and organs during embryogenesis, this study systematically analyzed Sox genes functionality in N. tilapia by using computational tools. In our study, phylogenetic analysis revealed that N. tilapia is most closely related to blue tilapia compared to other species. Sox genes are conserved in nature and share both acidic and basic properties as well as thermostable and hydrophobic in nature. The subcellular localization in N. tilapia indicated that majority of the Sox proteins are expressed in the Nucleus and Cytoplasm. Enrichment analysis explains the Sox genes’ role in cell differentiation, and biosynthesis process and acts as a molecular functional regulator. Significant differences in transcription binding sites were observed, highlighting the potential role of these regulatory regions in the regulation of Sox genes in N. tilapia. First time it is reported that Sox genes in N. tilapia have four major recombinant breakpoints that revealed phylogenetic segregation across several recombination fragments. In this primer, we aim to provide the reader with a comprehensive overview of Sox gene family in N. tilapia and to provide the functional properties of Sox genes for better follow-up in upcoming experiments for futuristic research.